Una dimensión regional del ciclo económico: El caso de Risaralda 1980 - 2002. (2021)
From the assumption that some regions may react with diferent force than others to the behaviors of the national macroeconomics variables, such as changes caused by the economic policy, variations in the relative prices and/or technological innovations, this document explore the characteristics of the Risaralda economic cycle in the 1980 – 2002 period. For this, it is evaluated in which measure the productive cycle in Risaralda has been related with the national pattern, or, if by the contrary, it has been fundamentally determined by particular events of the department and/or by the changes in the international economic conditions, specially in which has to do with the evolution of the international coffee market. It is found that the regional cycle has had a bigger average duration and a greater volatility in comparison to the national cycle, which confirms the initial hypothesis.